Cellular transplantation : from laboratory to clinic - Halberstadt, Craig; Emerich, Dwaine F. (Elsevier Academic Press, 2007)
There have been tremendous strides in cellular transplantation in recent years, leading to accepted practice for the treatment of certain diseases, and use for many others in trial phases. The long history of cellular transplantation, or the transfer of cells from one organism or region of the body to another, has been revolutionized by advances in stem cell research, as well as developments in gene therapy. Cellular Transplants: From Lab to Clinic provides a thorough foundation of the basic science underpinning this exciting field, expert overviews of the state-of-the-art, and detailed description of clinical success stories to date, as well as insights into the road ahead. As highlighted by this timely and authoritative survey, scale-up technologies and whole organ transplantation are among the hurdles representing the next frontier. The contents are organized into four main sections, with the first covering basic biology, including transplant immunology, the use of immunosuppressive drugs, stem cell biology, and the development of donor animals for transplantation. The next part looks at peripheral and reconstructive applications, followed by a section devoted to transplantation for diseases of the central nervous system. The last part presents efforts to address the key challenges ahead, such as identifying novel transplantable cells and integrating biomaterials and nanotechnology with cell matrices. Provides detailed description of clinical trials in cell transplantation Review of current therapeutic approaches Coverage of the broad range of diseases addressed by cell therapeutics Discussion of stem cell biology and its role in transplantation.